Сезонные и возрастные изменения содержания холестерина в головном мозгу бурозубок - Межжерин, В.А.; Финагин, Л.К. (Вестник зоологии, 1968)
The study of 111 specimens of S. araneus and 23 of S. minutus showed that cholesterol content in their brain in September is the least and characterized by a considerable variability. During the next months it increases and reaches the highest indices in December (twice as much as compared with September). A high cholesterol content in the brain is also observed during the next three months. But in April it considerably decreases in comparison with the winter months. It may be supposed that the compensator accumulation of cholesterol takes place in the brain, which is conditioned by a winter decrease of metabolically labile compounds (brain phospholipids and thiglycerides).